Apps in Time of Pandemic: Digital Usage and Gratifications in Transition towards #SmartCity - Basu, Surhita; Gharami, Baby (EAI Endorsed Transactions on Smart Cities, 2021)
INTRODUCTION: The study explores how during COVID-19 pandemic online apps helped people applying uses gratification paradigm to identify needs, usages and gratification of users. OBJECTIVES: The paper investigates how COVID-19 pandemic has affected the usage pattern of online apps? What is the gratification level of using online apps during COVID-19 pandemic? How users perceive the use of online apps during COVID-19 pandemic? METHODS: The study employs small scale snowball sampling survey across major cities of India addressing questions on comparative usage pattern of online apps before and during the pandemic, users’ gratification and users’ opinion of using online apps. RESULTS: Usage of few apps like news, video, health increased during the pandemic with frequency and intensity of usage. Users are concerned with misinformation spread through social media, demeaning family bonding due to high usage of apps, digital divide failing to provide enough job opportunities. CONCLUSION: Specific apps to deal with health emergencies should be developed along with mechanism against spread of misinformation and strategic attempts for digital inclusion.